Emeritus professors vision about students: learning from older professors - Felipe Trillo Alonso; María Ainoa Zabalza Cerdeiriña; Ana Parada Gañeta (Universitat Politècnica de València, 2015)
This work is part of a wider investigation developed  in  the  framework  of  the call for R&D of the Spanish Ministry of Science and Innovation which involved several Spanish and foreign universities. Its main objective was to recover the expertise  of  Emeritus  Professors  to make  it  available  to  the  university community. This article presents some data  regarding  beliefs  on  students expressing by 41 Emeritus Professors of  Spanish  and  foreign  universities.  Through  broader  reflections  on  the university, we focus on what specifically Emeritus Professors say about students, to develop, from their experience, a framework that allows us to rethink how we see the universitary students. The data presented here has been collected by semi-structured in depth interviews, from  which  we  have  conducted  an analysis of content. From this analysis conclusions are drawn about the more or  less  profound  transformations undergone by the university throughout the period covered by the career of these Emeritus and regarding different areas: from of which we underline the students.